2013
DOI: 10.1007/s10826-013-9877-0
|View full text |Cite
|
Sign up to set email alerts
|

Link Between Monitoring Behavior and Adolescent Adjustment: An Analysis of Direct and Indirect Effects

Abstract: The purpose of the current investigation was to explore whether monitoring behavior (i.e., parental solicitation, child disclosure, and parental involvement) was directly and indirectly (via parental knowledge and parent-youth openness) related to adolescent adjustment (i.e., antisocial behavior, substance use, and school grades). The sample consisted of 206 families with adolescents (ages 10–18 years) from predominantly low-income, high-risk neighborhoods. Monitoring behavior (parent reports), parental knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 37 publications
4
56
2
3
Order By: Relevance
“…While Keijsers et al (2010) show that solicitation is positively associated to parental knowledge, other studies with students in early and mid-adolescence STRUCTURAL RELATIONS BETWEEN SOURCES OF PARENTAL KNOWLEDGE found that it did not (Criss et al, 2015;Kerr et al, 2010). The current findings indicate that parental solicitation does not contribute to parental knowledge.…”
Section: The Relations Between Adolescent Disclosure Parental Solicicontrasting
confidence: 75%
See 1 more Smart Citation
“…While Keijsers et al (2010) show that solicitation is positively associated to parental knowledge, other studies with students in early and mid-adolescence STRUCTURAL RELATIONS BETWEEN SOURCES OF PARENTAL KNOWLEDGE found that it did not (Criss et al, 2015;Kerr et al, 2010). The current findings indicate that parental solicitation does not contribute to parental knowledge.…”
Section: The Relations Between Adolescent Disclosure Parental Solicicontrasting
confidence: 75%
“…Researchers tend to study only one type of adolescent behavior in relation to parental knowledge (Stavrinides et al, 2010). But, the associations between parental knowledge and its sources and adolescent adjustment may differ depending on the risk behavior that is studied (Criss et al, 2015). In this study, we first examined the associations between parental knowledge and its sources, adolescent disclosure, parental control, and parental solicitation.…”
Section: Current Studymentioning
confidence: 99%
“…The sample consisted of 206 families with adolescents who participated in the Family and Youth Development Project (Criss et al, 2015), a study of the predictors and outcomes of adolescent emotion regulation. Data were collected from both adolescents ( M age = 13.37 years, SD = 2.32, Age Range = 10–18 years; 51% female; 29.6% European American, 32% African American, 19.4% Latino American, 19% other ethnic groups) and their primary caregivers (83.3% biological mothers, 10.7% biological fathers, 2% grandparents, 4% other).…”
Section: Methodsmentioning
confidence: 99%
“…This error was consequential to the way in which parental monitoring tended to be operationalized, namely as what parents know about their child's daily whereabouts rather than what parents do to monitor their child's behavior. More recent studies conceptualize parental knowledge as resulting from monitoring activities, with some studies suggesting that the protective effect of parental monitoring runs entirely (Lippold et al 2014a) or partially (Criss et al 2015) through the amount of knowledge that monitoring generates. It should be noted, however, that a lack of conceptual clarity continues to blur the research field.…”
Section: Parental Knowledge Of Children's Offline Behaviormentioning
confidence: 99%